Mathematical Representation of Students in Solving Mathematic Problems Reviewed from Extrovert-Introvert Personality - Awaludin, Aulia Ar Rakhman; Selvia, Noni; Andrari, Finata Rastic (Universitas Pendidikan Ganesha, 2021)
In implementing mathematics learning in schools, educators must pay attention to five main competencies, namely problem solving, communication, connection, reasoning, and representation. Mathematical representation is a tool to convey students' algebraic thinking as an aid to construct their ideas about patterns and functions. This study aims to examine the mathematical representation of students in terms of introvert and extrovert personality types. To see the characteristics of mathematical representations in solving mathematical problems when viewed from the personality type of each student. This research method is descriptive qualitative. The number of schools and students who were sampled from this study was taken using a multistage sampling technique. The data collection instruments in this study were personality questionnaires, problem-solving tests, interviews, observations, and documents obtained from research subjects. The problem-solving analysis used is based on the Krulik and Rudnik steps. The personality types of extroverted students and introverted students do have different mindsets so that even though in some steps they use the same representation, their tendencies or habits represent problem-solving using different forms of representation. The personality types of extroverted students represent them more symbolically and almost all answers from extroverted students are closer to true when compared to introverted students.